EL RETABLO DEL SIGLO XVII EN CÓRDOBA - Raya Raya, María de los Angeles (Imafronte, 1989)
To Córdoba, the XVIIth century represents a stage of splnidour as far as regards retablemaking activity. This is a srage opened by the great main retable in the cathedral of córdoba, carved in marble according to a project by the Jesus Brarher Alonso Marías. Parish churches, like those in Santaella and Montemayor, are going ro follorit its example in the firsr half of the century. During this time, other schemes are going to assert themselves too as in certain retables in conventual Carmelite churches (an example: Sr. Joseph’s retable in Lucetiu). By the middle of the century, a clear evolution is observeti in the retable of Sr. Anne, in Montilla, a work by Bals de Escobar, the influence of wich we perceive in other works of this areu. It the last quarter of the century. the twisted column retable assert itself in Córdoba and other main places of its province, like Lucena. Francisco Hurtado Izquierdo, a real protagonist of the transition from the XVIIth to the XVIIIth century, became rrained here.